Multilevel optimal distinctiveness: Examining the impact of within‐ and between‐organization distinctiveness of product design on market performance - Bu, Juan; Zhao, Eric Yanfei; Li, Krista J.; Li, Joanna Mingxuan (Strategic Management Journal, 2022)
Abstract Research Summary This research develops a multilevel framework to study optimal distinctiveness (OD) at two levels. We distinguish between within‐organization distinctiveness and between‐organization distinctiveness of product design and examine how they independently and interactively influence performance. Analyzing a unique data set of 2,203 model‐year observations for automobiles sold in the U.S. market from 2001 to 2016, we found that while within‐organization distinctiveness of product design hurts market performance, between‐organization distinctiveness of product design increases market performance. Moreover, when between‐organization distinctiveness of product design is high, the negative impact of within‐organization distinctiveness of product design on performance is weakened. These findings contribute to OD research by improving the understanding of OD as a multilevel construct and elaborating on its contextual contingency. Managerial Summary How should multiproduct organizations design their products to achieve better performance? This article provides a multilevel perspective that encourages managers of multiproduct organizations to consider different frames of references when designing products. We suggest that a product's design should be consistent with the prototypical design of its organization, whereas the prototypical design of this organization should be different from the average design in the industry. We also found that an atypical design is more desirable if it is from an organization known for distinctive designs in its industry. Our findings help managers of multiproduct organizations achieve the optimal levels of design distinctiveness at both the product and organizational levels.